Modern Concurrency on Apple Platforms : Using Async/await with Swift - Kautsch, Andrés Ibañez (Apress, 2023)
Build solid software with modern and safe concurrency features. Concurrency is one of the hardest problems in computer science. For years, computer scientists and engineers have developed different strategies for dealing with concurrency. However, the original concurrency primitives are complicated and difficult to understand, and even harder to implement. Using the new async/await APIs in Swift, this book will explain how your code can abstract a lot of the complexity with a simpler interface so you never have to deal with concurrency primitives such as semaphores, locks, and threads yourself. This will allow you to write concurrent code that is easier to read, easier to write, and easier to maintain. These new APIs are deeply ingrained into Swift, offering compile-level features that will keep you from writing dangerous concurrent code. You'll start by exploring why concurrency is hard to implement in a traditional system. Explaining the definition of concurrency and what its primitives are will help you understand why they are hard to use correctly. These concepts will become clearer as you work through the sample projects. The book's focus then shifts exclusively to the new APIs, helping you understand how the integration of the system with the language itself makes it easier for you to write concurrent code without overstepping the bounds of the concurrency safe zone. By the end of the book, you'll have a solid foundation for working safely with concurrent code using the new async/await APIs. What You'll Learn Understand concurrency and its traditional problems Work with the new async/await API and all its features, from the basic usage and await keywords, to task groups and async sequences. Implement modern and safe concurrent code that you can start using right away Who This Book Is For Experienced iOS developers at a semi-senior or senior level. Knowledge on the Grand Central Dispatch is a bonus, but not required.